Tests Screening Writing Difficulty in Malayalam among Upper Primary Students - K. Abdul Gafoor (Int J Edu Sci, 2014)
Design of a screening test for identifying students with writing difficulty in Malayalam and validation thereof among upper primary students of Kerala is made to help schools to understand factors leading to such difficulty and to intervene with such students. A battery of tests was developed based on extant literature on screening tests, reviewed difficulties in writing Malayalam, and discrimination power of the draft tests. 135 students identified as writing difficult and 476 students normal on writing in grade 5 to 7 were identified with clear criteria. Scored by cut-points, the battery of tests comprising tasks on ordering words by vowels or consonants, spelling (identification), choosing signs and glides, combining words correctly (phonology), vocabulary (picture), using appropriate one word (morphology), dictation and story development significantly screen upper primary writing difficult students with around 90percent sensitivity and specificity.